Experimental miscellaneous involving the characterization of radon and natural uranium - De Lima, Jorge Luis Nepomuceno; Bonotto, Daniel Marcos [UNESP] (My University, 2012)
Radon (222Rn) is a colorless, odorless, tasteless, chemically inert and radioactive gas produced continuously in rocks and soils. It is genetically related to uranium (238U) in the 4n+2 decay series of radionuclides. Potential health hazards from radon and uranium in consuming water have been considered worldwide, with many countries adopting the guideline activity concentrations for drinking water quality recommended by WHO. High 222Rn concentrations occur in groundwater in many areas where wells are used for domestic water supply, inclusive in small rural water supplies. The major natural processes related to high radon concentration in groundwater include the low transmissivity zones, uranium content of the source rock, severe chemical weathering, hydrothermal solution, deposition, extensive fracturing and variations in stress in rocks associated with seismicity. Because uranium and radon exhibit quite variable physical properties, the detection of these radionuclides in natural systems like waters and rocks demands the use of specific techniques. This chapter reports the results of some laboratory experiments held with the aim of settling analytical protocols for performing the measurements of uranium and radon in rocks and waters. Alpha scintillation counting and gamma ray spectrometry with NaI(Tl) scintillation detector have been particularly focused as they are low-cost very traditional methods that yield satisfactory readings for the radioactivity due to uranium and radon in rocks and waters. Therefore, they are suitable for the development of environmental studies involving the radiation dose measurements with consequent implications for the human health hazards. © 2012 Nova Science Publishers, Inc. All rights reserved.